2019
DOI: 10.3389/fpsyt.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives on Psychiatric Comorbidity in Preschoolers With Autism Spectrum Disorders Receiving Publicly Funded Mental Health Services

Abstract: An increased prevalence of psychiatric comorbidity (PC) in individuals with Autism Spectrum Disorders (ASD) is consistently reported. While several studies have examined PC in school-aged children, adolescents and adults with ASD, investigations on PC in preschoolers are less common. In this study, we explore the prevalence and the type of PC in a sample of 989 preschoolers with ASD through the DSM-Oriented Scales (DOS) of the Child Behavior Checklist (CBCL 1½-5) and their possible links with the core features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 123 publications
(154 reference statements)
1
17
0
1
Order By: Relevance
“…A total of 107 females matched to 107 males one by one for chronological age (±6 months) and non-verbal IQ (±6 points) were examined. All the participants were selected from an initial sample of 989 preschoolers with and without non-verbal IQ impairment (mean age, 44.0 months; SD, 13.8 months; range, 16–75 months) examined in the preliminary analysis section of this study and investigated in depth in previously published research (Muratori et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 107 females matched to 107 males one by one for chronological age (±6 months) and non-verbal IQ (±6 points) were examined. All the participants were selected from an initial sample of 989 preschoolers with and without non-verbal IQ impairment (mean age, 44.0 months; SD, 13.8 months; range, 16–75 months) examined in the preliminary analysis section of this study and investigated in depth in previously published research (Muratori et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we adopted the borderline clinical elevation cutoff score ( T score ≥60 for summary scales and T score ≥65 for DOS), according to previous studies on screening (Muratori et al, 2011 ; Narzisi et al, 2013 ; Rescorla et al, 2015 ) and PC (Llanes et al, 2018 ; Muratori et al, 2019 ) in young children with ASD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When using the parent‐report CBCL, the overall anxiety prevalence across five studies ranged from 16.7 to 31.8% [Iao, Yu, & Wu, 2020; Johnson, DeMand, & Shui, 2015; Muratori et al, 2019; Snow & Lecavalier, 2011; Vasa et al, 2013]. Two of these studies reported a greater prevalence of anxiety compared to an ON group (26 vs. 17%, Iao et al, 2020; 31.8 vs. 22.1%, Snow & Lecavalier, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Studies including a broader age of children (e.g., 4–18 years) were included only if age‐specific subgroup analyses were conducted with children under 6 years when examining prevalence, correlates, and treatment. Seven studies included children with an age range up to 8 years because the mean age of children in these studies was under 6 years old [Driscoll et al, 2020; Goldman et al, 2011; Keen, Adams, Simpson, Den Houting, & Roberts, 2019; Lei, Sukhodolsky, Abdullahi, Braconnier, & Ventola, 2017; Muratori et al, 2019; Sukhodolsky et al, 2020; Wilson, Manangan, Dauterman, & Davis, 2014]. (b) ASD and either co‐occurring anxiety symptoms or disorders were present in the child and the methods to assess ASD and anxiety were explicitly reported.…”
Section: Methodsmentioning
confidence: 99%